2013
DOI: 10.1021/la401981b
|View full text |Cite
|
Sign up to set email alerts
|

Tribology and Stability of Organic Monolayers on CrN: A Comparison among Silane, Phosphonate, Alkene, and Alkyne Chemistries

Abstract: The fabrication of chemically and mechanically stable monolayers on the surfaces of various inorganic hard materials is crucial to the development of biomedical/electronic devices. In this Article, monolayers based on the reactivity of silane, phosphonate, 1-alkene, and 1-alkyne moieties were obtained on the hydroxyl-terminated chromium nitride surface. Their chemical stability and tribology were systematically investigated. The chemical stability of the modified CrN surfaces was tested in aqueous media at 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 61 publications
0
28
0
7
Order By: Relevance
“…[53] It has been reported that the monolayer obtained by the reaction of alkynes with hydroxyl-terminated surfaces shows ah igher stabilityc ompared to that obtained by the reactions of silanes, phosphonates, and alkenes. [54] The contact angles of water droplets on TNA were measured to verify the changei nt heir surfaceh ydrophilicity. [55] As showni nF igure 2b,t he contact angle on the nanotube arrays changed from 08 to 148 after the PA treatment, implying that TNAb ecamem ore hydrophobic.…”
Section: Synthesis and Characterizationmentioning
confidence: 89%
“…[53] It has been reported that the monolayer obtained by the reaction of alkynes with hydroxyl-terminated surfaces shows ah igher stabilityc ompared to that obtained by the reactions of silanes, phosphonates, and alkenes. [54] The contact angles of water droplets on TNA were measured to verify the changei nt heir surfaceh ydrophilicity. [55] As showni nF igure 2b,t he contact angle on the nanotube arrays changed from 08 to 148 after the PA treatment, implying that TNAb ecamem ore hydrophobic.…”
Section: Synthesis and Characterizationmentioning
confidence: 89%
“…showed in a comparative study of various attachment chemistries that silane monolayers on hydroxy‐terminated CrN surfaces are unstable in aqueous media of various pH values (Figure 8). 50 If monolayers of higher stability are desired, then those derived from alkyl phosphonates (Section 3), catechol (Section 5), and alkenes/alkynes (Section 6) are typically more promising. Aureau et al.…”
Section: Silanesmentioning
confidence: 99%
“…2 -step II). We chose this neutral pH environment in order to minimize 1) siloxane adlayer etching from the substrate (Pujari et al, 2013), and 2) the population of reactive PMB amine moieties in their basic RNH 2 form (versus inactive protonated form RNH 3 þ ) to prevent multi-amine site attachment of PMB (see Supporting information) -as maximizing the number of exposed free amine groups was shown to correlate with higher endotoxin removal/binding capacity (Shoji, 2003). Both successful transformations were characterized using angle-resolved XPS following the signal evolution of the characteristic elements of quartz (Si and O), OEG-TTTA and MEG-TFA surface residues (C and F), and PMB probe (N).…”
Section: Biosensing Platform Preparation and Characterizationmentioning
confidence: 99%